2023
DOI: 10.1093/sleep/zsad072
|View full text |Cite
|
Sign up to set email alerts
|

Good sleep is a mood buffer for young women during menses

Abstract: Study Objectives We sought to elucidate the interaction between sleep and mood considering menstrual cycle phase (menses and non-menses portions of the cycle) in 72 healthy young women (18 – 33 y) with natural, regular menstrual cycles and without menstrual-associated disorders. This work fills a gap in literature of examining mood in context of sleep and menstrual cycle jointly, rather than individually. Methods Daily subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Objective and subjective sleep outcomes may reflect the different aspects of sleep. 35 Some reports have shown that there is usually a discrepancy between the subjective and objective measures of sleep. 36,37 Despite this, in female athletes with regular menstrual cycles, poor subjective sleep quality is associated with an increased arousal index during menstruation.…”
Section: Discussionmentioning
confidence: 99%
“…Objective and subjective sleep outcomes may reflect the different aspects of sleep. 35 Some reports have shown that there is usually a discrepancy between the subjective and objective measures of sleep. 36,37 Despite this, in female athletes with regular menstrual cycles, poor subjective sleep quality is associated with an increased arousal index during menstruation.…”
Section: Discussionmentioning
confidence: 99%
“…Shuster et al studied 72 healthy individuals who reported mood and sleep daily across two menstrual cycles using digital diaries [ 9 ]. Objective sleep measures were estimated during participants’ second cycle.…”
mentioning
confidence: 99%